(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: In this research study, we explore the fluctuating asymmetry (FA) of palate Camelus hybrids and their parental species (dromedary and Bactrian). Materials and Methods: We studied a sample of pictures from 27 adult skulls of pure Camelus dromedarius (n = 13), Camelus bactrianus (n = 7), and their crosses (n = 7), from two different collections. A set of 11 semilandmarks was located on the palatal region and was studied by means of geometric morphometric methods. The asymmetric variation was analyzed and evaluated for allometric effects, and variation among these three groups was studied using a canonical variates analysis. Results: Among hybrids, there appeared a significantly lower amount of FA in comparison to the parental species, which may reflect the lower levels of genetic stress and higher levels of directional asymmetry, which may suggest the presence of strongly transgressive mastication compared to pure species. Conclusion: Camel hybrids would present increased developmental stability and better adaptation over those of parenteral lines. J. Adv. Vet. Anim. Res., 7(4): 663-668, Dec 2020 http://doi.org/10.5455/javar.2020.g465